Predictive capacity of the brain natriuretic peptide in the screening of heart failure in a high altitude population - Calderón-Gerstein, Walter; Bruno-Huamán, Astrid; Damián-Mucha, Milagros; Huayllani-Flores, Lizet (Respiratory physiology & neurobiology, 2021)
•BNP values are increased in cardiac and non – cardiac conditions at high altitude.•Usual BNP cut-off of > 100 pg/mL has good sensitivity but very low specificity for heart failure diagnosis at altitude.•Right-sided heart failure, pulmonary hypertension and interstitial lung disease are associated with higher BNP levels at high altitude•New cut-off values, different from those used at sea level, are needed to improve BNP predictive accuracy for heart failure identification at high altitude. Heart failure (HF) is growing in importance as a significant cause of disease and mortality. When It is suspected, it can be ruled out if BNP values are below 100 pg/mL. Diagnostic certainty can be obtained if echocardiogram shows reduced ejection fraction, diastolic dysfunction or right-sided heart disease. Physiological changes at high altitude are known to affect BNP values. This study pretends to evaluate BNP values when used for HF diagnosis in Huancayo, Perú, a high altitude population located at 3,250 m above sea level. This is a cross-sectional, diagnostic test type study. A total of 83 medical charts of patients with suspected HF, admitted to the Emergency Room and Internal Medicine Service of Ramiro Prialé Prialé National Hospital, were reviewed. Data processing was performed with SPSS program for Windows version 21.0. Pearson's Chi Square test was used for categorical variables analysis and ANOVA for continuos variables. P values under 0.05 were considered significant. Medium age was 74 years. Patient’s characteristics that were associated with confirmed HF and high BNP levels were the following: presence of fatigue, night cough, elevated heart rate, shortness of breath, history of lung fibrosis and decreased oxygen arterial saturation (p < 0.05) Pulmonary hypertension, mitral and tricuspid regurgitation, and cor pulmonale were also associated with higher BNP levels. Most subjects had BNP values >100 pg/mL, with low specificity for HF diagnosis (11.5 %). Individuals without heart failure had mean BNP values above 300 pg/mL; while individuals with cor pulmonale had a mean of 975 pg/mL. BNP values were high in patients with or without HF. A cut-off point of ≥130pg/mL is proposed to increase specificity. The predictive capacity of BNP for HF identification at this high altitude population is low because of a high number of false positive results.